Implementation of the INTERGROWTH‐21st Project in Oman. (17th May 2013) - Jaffer, YA; Al Abri, J; Abdawani, J; Knight, HE; Cheikh Ismail, L; ,
Abstract : The Middle Eastern site in the INTERGROWTH‐21 st Project was Muscat, the capital city of Oman, with approximately 10 500 births per year. The sample for the Newborn Cross‐Sectional Study (NCSS) was drawn from two hospitals covering 96% of the region's births. The Fetal Growth Longitudinal Study (FGLS) sample was recruited from four primary health facilities serving Khoula Hospital, using the eligibility criteria in the INTERGROWTH‐21 st protocol. Special activities to encourage participation in this population included local advocacy campaigns to encourage early antenatal booking and ultrasound dating in the population. The major challenges at the site were the recruitment of sufficient numbers of women at an early gestational age, and the timely measurement of all newborns within 12 hours of birth. Many individuals and institutions collaborated effectively over a period of several years on these studies, which required careful planning and close monitoring for their successful implementation.